Development of a Device for Displaying on an Additional Screen the Parameters Read from the Vehicle’s on Board Computer : Array - Laszlo, Barothi; Voicu, Daniela; Stoica, Ramona-Monica; Deleanu, Lorena (Journal of Danubian Studies and Research, 2021)
Present paper aims to present the steps of developing a prototype used for the display of several functional parameters which does not normally appear on the dashboard of an automobile. Data is collected from the vehicle CAN bus, follow-up processed with a MCP2515 microcontroller and a ATMEGA328P and finally displayed on a color touchscreen. The prototype is a Plug&Play device, which can easily be connected to the vehicle’s OBD2 socket, from where the data is collected. The parameters are shown in an interactive manner, by displaying one or multiple parameters at a time, on a single page.